Loading effect–induced broadband perfect absorber based on single-layer structured metal film. (July 2017) - Lin, Keng-Te; Chen, Hsuen–Li; Lai, Yu-Sheng; Yu, Chen-Chieh; Lee, Yang-Chun; Su, Pao-Yun; Yen, Yu-Ting; Chen, Bo-Yi
Abstract: A broadband perfect absorber based on loading effect–induced single-layer/trench-like thin metallic (LISTTM) structures is demonstrated. These LISTTM structures take advantage of both surface plasmon resonance and three-dimensional cavity effects to provide efficient, tunable, polarization-insensitive absorption from the ultraviolet (UV) to the infrared (IR) regime. The optimized hole-width of the LISTTM arrays was approximately one half of the designed wavelength. Therefore, even when the designed absorption band was in the visible regime, the feature sizes of the LISTTM structure could remain on the order of several hundred nanometers. Moreover, the loading effects, which were generated during the etching and deposition processes, further improved the maximum absorption to greater than 95% and widened the absorption bandwidth of the structures significantly. These LISTTM structures exhibited superior photothermal performance; they also displayed very low emissivity, thereby decreasing heat dispersion through thermal radiation. Therefore, the LISTTM arrays could efficiently absorb light of higher photon energy in the UV, visible, and near-IR regimes, effectively conduct the generated heat through the continuous metal films, and barely disperse any heat through thermal radiation. Accordingly, these attractive properties suggest that such LISTTM absorbers might have promising applications in many fields related to energy harvesting. Graphical abstract: Highlights: We proposed a perfect absorber based on loading effect–induced single-layer/trench-like thin metallic (LISTTM) structures. The LISTTM arrays could efficiently absorb light in the UV, visible, and near-IR regimes. They could also effectively conduct the generated heat through the continuous metal films. The LISTTM arrays barely disperse any heat through thermal radiation. LISTTM absorbers might have promising applications in many fields related to energy harvesting.